El impacto del deporte en el desempeño académico : el caso de la Universidad de los Andes (2017)
"Physical activity has multiple positive effects on the human well being. Nevertheless, Colombia still has deficiencies in terms of the infrastructure and the promotion policies regarding this sector. Using the data of the students of the Universidad of the Andes, the relationship between sport practice and academic achievement is analyzed in this study. Therefore, this work studies the impact that frequency and intensity of sport practice of students have on their academic achievement. It was found that while being part of a university sports team didn't have a significant effect on academic achievement, the practice of sports in general does have a positive and significant effect on the GPA." -- Tomado del resumen.